ChemInform Abstract: Fluorous Bispidine: A Bifunctional Reagent for Copper‐Catalyzed Oxidation and Knoevenagel Condensation Reactions in Water. Issue 7 (January 2016) - Ang, Wei Jie; Chng, Yong Sheng; Lam, Yulin
Abstract: Fluorous bispidines are prepared and used as ligands and proton sponges in aerobic oxidation, Knoevenagel condensation, and tandem oxidation/Knoevenagel condensation.